(3aJM GdGbaGd hMd GdCTcGd HTQM dGjeI GdCaYGds - (3LeGd GdOjf eMeO Hf YeQ Hf eHGQc HMQb GdMVQeis; (3eMeO Hf YHO Gddg, GHf eGdc GdWGFj GdLqjGfj, CHh YHO Gddg, LeGd GdOjf,J (B672 (3g` s ((3WjH Hf CHj HcQ Hf WjH Hf CHj HcQ s)
(3ChdgG (B:s
(3GdMeO ddg GdeJUQa bHd Ydd GdJUQjahHYO ahabfi Gddg Cf TQMJ GdbUjOI GdeSeGg CHfjI GdCaYGd ai Yde GdJUQja ddEeGe GHf eGdc s
(3BNQgG (B:s
(3ai TQM bhd GdfGXe (B: (3hCf jjSQ di SYjkG Cchf Hg eSJHTQkG LPdkG dGHGSQkG hLdG Mbb Gddg dg eG QLGg Hefg hcQeg Bejf s
(3Vef eLehY , JQJjHgG (B: (3ef U (B1 - (3U(B92s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ CHjGJ GdGejI HGdMeQI s
(3hYdi GdhQbI GdChdi JbjjOGJ cKjQI s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
Keywords: (3GdUQas